Green Tea Catechins for Prostate Cancer Prevention: Present Achievements and Future Challenges - Valeria Naponelli; Ileana Ramazzina; Chiara Lenzi; Saverio Bettuzzi; Federica Rizzi (MDPI AG, 2017)
Green tea catechins (GTCs) are a family of chemically related compounds usually classified as antioxidant molecules. Epidemiological evidences, supported by interventional studies, highlighted a more than promising role for GTCs in human prostate cancer (PCa) chemoprevention. In the last decades, many efforts have been made to gain new insights into the mechanism of action of GTCs. Now it is clear that GTCs' anticancer action can no longer be simplistically limited to their direct antioxidant/pro-oxidant properties. Recent contributions to the advancement of knowledge in this field have shown that GTCs specifically interact with cellular targets, including cell surface receptors, lipid rafts, and endoplasmic reticulum, modulate gene expression through direct effect on transcription factors or indirect epigenetic mechanisms, and interfere with intracellular proteostasis at various levels. Many of the effects observed in vitro are dose and cell context dependent and take place at concentrations that cannot be achieved in vivo. Poor intestinal absorption together with an extensive systemic and enteric metabolism influence GTCs' bioavailability through still poorly understood mechanisms. Recent efforts to develop delivery systems that increase GTCs' overall bioavailability, by means of biopolymeric nanoparticles, represent the main way to translate preclinical results in a real clinical scenario for PCa chemoprevention.